The effect of rabeprazole alone or in combination with H2 receptor blocker on intragastric pH: A pilot study - Murat TÖRÜNER,; Mehmet BEKTAŞ,; Hülya ÇETİNKAYA,; İrfan SOYKAN,; Ali ÖZDEN, (Turkish Journal of Gastroenterology, 2019)
-